The Role of Interactive Pedagogy for Educational Reform - Ergashi, Murodova Gulnora; Muhidin, Nurmuhammadova Gulnoza (Bumi Publikasi Nusantara, 2025)
This article investigates the role of interactive pedagogy as a catalyst for educational reform, emphasizing the need for innovation in teaching methods, curricular design, and teacher development to meet contemporary educational demands. It aims to identify how pedagogical innovations can enhance the quality and effectiveness of the teaching-learning process. The study employs a qualitative analytical approach, reviewing existing literature and theoretical models related to pedagogical systems, innovation theory, and teacher readiness. Comparative analysis is used to explore two primary approaches for improving pedagogical systems: intensive (internal restructuring) and extensive (integration of external resources and technologies). The analysis reveals that interactive pedagogy—defined as the strategic use of creative, student-centered, and technology-integrated methods—improves the adaptability and responsiveness of educational systems. It fosters teacher creativity, promotes student engagement, and supports the holistic development of learning environments. The study underscores the transformative potential of interactive pedagogy in creating more dynamic, inclusive, and future-ready education systems. It calls for systemic support in teacher training, curriculum development, and policy formulation to embed innovation as a core element of educational reform.